City Indian : Native American Activism in Chicago, 1893-1934 - LaPier, Rosalyn R. (Book collections on Project MUSE., 2015)
In City Indian, Rosalyn R. LaPier and David R.M. Beck tell the engaging story of American Indian men and women who migrated to Chicago from across America. From the 1893 World's Columbian Exposition to the 1934 Century of Progress Fair, American Indians in Chicago voiced their opinions about political, social, educational, and racial issues. City Indian focuses on the privileged members of the American Indian community in Chicago who were doctors, nurses, business owners, teachers, and entertainers. During the Progressive Era, more than at any other time in the city's history, they could be f.